Potential of agricultural technologies and innovations to overcome humanitarian challenges cause by climate change in West Africa - Kpadonou, Gbedehoue Esaie; Ganyo, Kyky Désiré; Segnon, Alcade C.; Lamien, Niéyidouba; Zougmoré, Robert B. (2023)
The 14th edition of the biannual National Forum for Scientific and Technological Innovations (FRSIT 2023) organized by the Government of Burkina-Faso focused on ‘’Humanitarian Challenges in Africa: Contribution of scientific research and innovation for sustainable solutions’’. The report documents the achievements and lessons learnt from CORAF’s participation in FRSIT 2023. It also presents an analysis of how selected technologies and innovations generated by CORAF members that have the potential to prevent or overcome humanitarian challenges cause by climate change in West-Africa using the improved ALNAP’s framework for evaluating humanitarian innovations. Two main activities were organized during the FRSIT: (i) Exhibition of technologies and innovations developed by the National Agricultural Research Systems (NARS) of CORAF and (ii) a Side-Event on ‘’Potential of Technologies and Innovations generated by CORAF to meet climate change challenges, and strategies for making them available to users’’. Over 145 persons visited CORAF’s stand with more than 50% willing to purchase some of the exposed technologies and innovations. On the other hand, more than 150 persons participated into the side-event. Ten technologies or innovations were presented, from which five were selected by the participants: (i) Improved FBT tomato varieties, (ii) Orange colored-fleshed sweet potato, (iii) Feed production processes based on mango residues, (iv) Cotton Particleboard and (v) Improved fish cages. All the technologies and innovations recorded a potential for preventing or overcoming more than 70%, with orange-colored fleshed sweet potato being the prominent technology, followed by improved cage fish and improved FBT tomato variety and finally the two remaining cotton particle-board and feed production processes based on mango residues. More than 93% of the participants showed their willingness to acquire at least one of these technologies for their activities.